2013
DOI: 10.1080/01626620.2013.806231
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Educators as Learners: How Supervisors Shape Their Pedagogies by Creating and Using Classroom Videos with Their Student Teachers

Abstract: Although classroom video is well recognized as a valuable reflective resource for student teachers, we know very little about how university supervisors' pedagogical practices are shaped by creating and using videos with their student teachers. This study explored how 12 supervisors developed greater stances of inquiry toward their practices as they experimented with video and shared their experiences with peers. Patterns in project meeting and interview transcripts revealed how these experiences not only enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…This study reports similar findings to prior research that has found supervisors receive little preparation for and ongoing development of their practice (Danielowich & McCarthy, 2013;McCormack et al, 2019). While Hillside University did provide some supervisor training, it was insufficient to prepare supervisors for their work and led them to rely on peer networks and career experience to develop roles and praxis.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This study reports similar findings to prior research that has found supervisors receive little preparation for and ongoing development of their practice (Danielowich & McCarthy, 2013;McCormack et al, 2019). While Hillside University did provide some supervisor training, it was insufficient to prepare supervisors for their work and led them to rely on peer networks and career experience to develop roles and praxis.…”
Section: Discussionsupporting
confidence: 81%
“…This expanded supervisor role has implications for supervisor knowledge and skills as well as how supervisors acquire such knowledge and develop such skills. Unfortunately, supervisors receive very little training (Danielowich & McCarthy, 2013) and feedback on their performance (Conderman, Katsiyannis, & Franks, 2001). Furthermore, as largely graduate students and adjunct faculty (Baecher, McCormack, & Kung, 2014;Conderman, Morin, & Stephens, 2005;Zeichner, 2010), supervisors can be seen as or feel like they are outsiders to the university (Slick, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Video recordings to monitor and evaluate the success of student teachers (also known as teacher candidates) have been used for more than 20 years in teacher education (Kpanja, 2002; Olivero, 1980). Teacher candidate’s lessons are captured through video recording and are used by the university supervisor to improve the quality of their instruction (Danielowich & McCarthy, 2013). Video recordings are considered an important part of the learning process and ultimately a tool that can be used to show the growth and development of a candidate during the field experience.…”
Section: Discussionmentioning
confidence: 99%
“…Some have never video recorded themselves teaching before whereas others have completed class assignments which required them to video record their teaching and reflect upon its effectiveness. While it may be an awkward process for students to watch themselves on camera, research supports using video recording as a powerful pedagogical tool to facilitate teacher candidates' self-reflection and growth (Baecher, McCormack, & Kung, 2014;Calandra, BrantleyDias, Lee, & Fox, 2009;Danielowich & McCarthy, 2013;Tripp & Rich, 2012).…”
Section: Using Video and Video Considerations Teacher Candidate Skillmentioning
confidence: 99%